LDL-C/HDL-C ratio and risk of all-cause mortality in patients with intracerebral hemorrhage. (2nd October 2016) - You, Shoujiang; Zhong, Chongke; Xu, Jiaping; Han, Qiao; Zhang, Xia; Liu, Huihui; Zhang, Yanlin; Shi, Jijun; Huang, Zhichao; Xiao, Guodong; Zhang, Chunyuan; Cao, Yongjun; et al.
Abstract : Background: The low-density lipoprotein cholesterol/high-density lipoprotein cholesterol (LDL-C/HDL-C) ratio has been recognized as a strong risk predictor of cardiovascular diseases. However, the association between the LDL-C/HDL-C ratio and the prognosis of acute intracranial hemorrhage (ICH) is unclear. Thus, we prospectively investigated whether a low LDL-C/HDL-C ratio could predict all-cause mortality and whether LDL-C/HDL-C ratio is superior to traditional lipid profiles in predicting mortality among Chinese patients with acute ICH. Methods: A prospective cohort study of 356 patients with acute ICH was conducted, and the mean follow-up time point was 80.4 days. Participants were divided into four categories based on LDL-C/HDL-C ratio quartiles. Three-month outcomes were evaluated by in-person or telephone interviews with patients or their family members. The end point was three-month mortality from all causes. Results: Forty-seven deaths from all causes were documented. The multivariate analysis found that LDL-C/HDL-C ratio [hazard ratio (HR) = 0.49, p = 0.008] and LDL-C (HR = 0.27, p = 0.044) were significantly associated with all-cause mortality. The Kaplan–Meier curves show that patients in the lowest quartiles had the highest cumulative incidence rates (log-rank p = 0.027). After adjusting for covariates, a low LDL-C/HDL-C ratio was associated with a 3.55-fold increase in the risk of all-cause mortality (HR, 3.55 [95% confidence interval, 1.04–12.14]; P -trend = 0.011) when the highest and lowest quartiles were compared. The C-statistic of the LDL-C/HDL-C ratio was significantly larger than other traditional lipid profiles (all p < 0.05). Conclusions : A low LDL-C/HDL-C ratio was independently associated with an increased risk of all-cause mortality at three months in patients with ICH. Moreover, the LDL-C/HDL-C ratio appeared to be a best lipid predictor of all-cause mortality than traditional lipid profiles.